Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
Given Below.
Explanation:
(a)
[tex]x^2 - 12x = 45[/tex]
[tex]x^2 - 12x -45 = 0[/tex]
[tex]x^2 - 15x + 3x - 45 = 0[/tex]
[tex]x ( x-15) + 3 ( x - 15) = 0[/tex]
[tex](x+3)(x-15) = 0[/tex]
[tex]x = -3 , 15[/tex]
(b)
[tex]x^2 - 6x = 7[/tex]
[tex]x^2 - 6x -7 = 0[/tex]
[tex]x^2-7x + x -7 = 0[/tex]
[tex]x(x-7)+1(x-7) = 0[/tex]
[tex](x+1)(x-7) =0[/tex]
[tex]x = -1, 7[/tex]
1. )
[tex]x^{2} -12x=45\\x^{2} -12x-45 = 0\\(x-15)(x+3) = 0\\x = -3, 15[/tex]
2. )
[tex]x^{2}-6x=7\\x^{2} -6x-7=0\\(x-7)(x+1) = 0\\x = -1, 7[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.